1982
DOI: 10.1520/jfs12199j
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Phencyclidine and Its Analogues at Low Concentrations in Urine by Selected Ion Monitoring

Abstract: This paper presents retention behavior and mass spectra of eluting peaks for twelve phenyl and thienyl analogues of phencyclidine (PCP) as well as PCP itself. An on-column decomposition product common to all thienyl analogues is described. Finally, a practical analytical procedure is given for the detection and identification of these compounds in low (under 5 mg/mL) concentrations in urine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1983
1983
2000
2000

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Several methods have been reported for the detection of phencyclidine and related compounds in biological fluids. Kelly et al (148) identified phencyclidine and its analogues at low concentrations in urine by selected ion monitoring and Budd (149) used TLC for the analysis of l-(l-phenylcyclohexyl)pyrolidine in urine. EMIT and RIA procedures have been described for the detection of phencyclidine in biological fluids (150,152).…”
Section: {26)mentioning
confidence: 99%
“…Several methods have been reported for the detection of phencyclidine and related compounds in biological fluids. Kelly et al (148) identified phencyclidine and its analogues at low concentrations in urine by selected ion monitoring and Budd (149) used TLC for the analysis of l-(l-phenylcyclohexyl)pyrolidine in urine. EMIT and RIA procedures have been described for the detection of phencyclidine in biological fluids (150,152).…”
Section: {26)mentioning
confidence: 99%